2022
DOI: 10.1097/mcc.0000000000001009
|View full text |Cite
|
Sign up to set email alerts
|

Prone positioning of nonintubated patients with acute hypoxemic respiratory failure

Abstract: Purpose of review Since the early pandemic, prone positioning has been broadly utilized for nonintubated patients (so-called ‘awake prone positioning, APP’) with coronavirus disease 2019 (COVID-19) induced acute hypoxemic respiratory failure (AHRF). Recent findings Numerous clinical studies have been conducted to investigate the effects of APP on oxygenation, intubation, and mortality. However, several questions remain unclear, such as the patient popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The application of APP has shifted from patients undergoing vertebral body surgery, awake fiber-optic intubation, and lung transplantation [ 6 8 ] to non-intubated ARDS patients, which was supported by clinical guidelines and expert consensus statements [ 9 – 11 ]. The optimal duration of APP sessions remains uncertain, but previous studies indicated at least 8 h of daily prone position may be beneficial [ 2 , 12 ]. A recent meta-analysis of over 4,000 COVID-19 patients revealed that the actual duration of APP varied significantly, ranging from 1–2 h to 8–10 h per day [ 13 ], which may potentially affect the effectiveness of treatment [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of APP has shifted from patients undergoing vertebral body surgery, awake fiber-optic intubation, and lung transplantation [ 6 8 ] to non-intubated ARDS patients, which was supported by clinical guidelines and expert consensus statements [ 9 – 11 ]. The optimal duration of APP sessions remains uncertain, but previous studies indicated at least 8 h of daily prone position may be beneficial [ 2 , 12 ]. A recent meta-analysis of over 4,000 COVID-19 patients revealed that the actual duration of APP varied significantly, ranging from 1–2 h to 8–10 h per day [ 13 ], which may potentially affect the effectiveness of treatment [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In particular, awake PP (APP), which involves placing non-intubated patients in PP, has become popular due to its ease of implementation and the overwhelming need for avoiding intubation. [5][6][7] This review will discuss relevant findings from recent publications on the use of PP and APP for patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygenation improvement and changes in the lung ultrasound findings may help to identify those individuals more likely to avoid intubation. 25 …”
mentioning
confidence: 99%